Kinetic evaluation of sonicated food waste in continuously stirred tank reactor - Md Sabiani, Nor Habsah; Tajarudin, Husnul Azan; Wan Ab Karim Ghani, Wan Azlina; Idris, Azni; Samsu Baharuddin, Azhari (I W A Publishing, 2022)
This work aimed to evaluate the process performance and stability of the anaerobic digestion of sonicated food waste (SFW) by determining the kinetic parameters using Monod, Contois, Modified Stover-Kincannon, and Grau second-order multicomponent substrate removal kinetic models. The anaerobic digestion was conducted on the sonicated food waste (SFW) in a 13 L continuously stirred tank reactor (CSTR) with a stepwise organic loading rate (OLR) ranging from 1.5 to 3.5 gCOD/L.day. The experimental works were carried out in two stages (start-up then followed by semi-continuous). The ultrasonic pretreatment was performed by sonicating the food waste slurry for 10 minutes at a 20 kHz frequency and specific energy input of 25,997 kJ/kg TS. The process performance, as well as acceptable stability in the SFW digester, provided satisfactory predictions with Monod, Modified Stover-Kincannon, Grau second-order multicomponent substrate removal, and Contois kinetic models. A significant relationship was seen between the predicted and experimental data with correlation coefficients (R2) ranging from 0.893 to 0.996. In this study, the Monod model with R2 = 0.996 indicates the most suitable model for understanding the kinetic parameters of the anaerobic system in the CSTR which digests the sonicated food waste (SFW) slurry.